THE IMPACT OF TRAINING, EMPLOYEE LOYALTY AND ORGANIZATIONAL CULTURE ON THE WORK ACHIEVEMENT : LITERATUR REVIEW - Ramdhani, Abel; Hadi, Syamsul; Purnamarini, Tri Ratna (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This paper aims to comprehend how training, employee loyalty, and organizational culture affect workers' achivment. An in-depth explanation of the elements that directly improve worker performance will be provided by this article. A systematic literature review (SLR) is used in this process. 30 papers were found through the use of the keywords